Regional investment and individual redistribution in a federation - Sebastian G. Kessing; Benny Schneider (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2014)
We study the strategic incentives of regional governments to allocate their budget to public investment and to public consumption expenditures against the background of an incentive-compatible redistribution policy set by the central government. Regional investment changes the productivity distribution in the economy, which aects the design of the optimal tax-transfer system by the central government. The strategic incentives can dier between rich and poor regions depending on the nature of the investment. Rich and poor regions both have strategic incentives to reduce investment which increases the productivity of all individuals in a region. For investment which only increases the productivity of a part of the population, rich regions have reduced investment incentives, whereas poor regions have increased strategic incentives to invest. Our results hint at potential benets of appropriate dierentiation of matching grants.
Keywords: H21; H72; H77; H54; 330; optimal income taxation; regional investment; fiscal federalism